Boundary layer flow and heat transfer of Cu-Al2O3/water over a moving horizontal slender needle in presence of hydromagnetic and slip effects. (April 2021) - Aladdin, Nur Adilah Liyana; Bachok, Norfifah; Pop, I.
Abstract : Research on boundary layer flow and heat transfer has been growing since their importance in industrial and technological processes has been recognized. The boundary layer flow over a horizontally and vertically slender (thin) needle with irregular size has created interest among researchers due to its infinite use in biomimetics field, biomedical, aerodynamics, and engineering purposes. The intention here is to study the two-dimensional steady hybrid nanofluid over a slender horizontal needle with water as its base, copper (cu), and alumina oxide (Al2 O3 ) as the combination of nanoparticles in the presence of hydromagnetic and slip effect in the flow. A partial differential equation (PDEs) was set to govern the fluid flow model. Through similarity requirement, the PDE is transformed into ordinary differential equations (ODEs) and analysed using bvp4c in MATLAB 2019a. The influence of hydromagnetic (MHD), M, slip effect, σ, needle thickness, c, and nanoparticle volume fraction, φ on velocity, f  ′ ( η ), temperature, θ ( η ), skin friction coefficient, C f and local Nusselt number, Nu x are clearly presented. Throughout the study, it shows that duality of solutions presents in a certain range when ԑ c  <  ԑ  ≤  − 1 and unique solution at ԑ  >  − 1. The range on the dual solutions broadens as σ increased, which contradicts with M and c that decreases as both of these values increased. Hence, a stability analysis is imposed. The reduction on skin friction between the needle and fluid can been seen when values of M, σ and c increased. Meanwhile, it also noted that the heat transfer rate on the needle surface increased drastically when σ is increased while opposite trait is found for M and c. hybrid nanofluid possesses better results in increasing the C f and heat transfer rate compared to nanofluid.